Psychology 101 1/2 : The unspoken rules for success in academia - Sternberg, Robert J. (Washington D.C. American Psychological Association, 2004)
In Psychology 101?, Yale professor Robert J. Sternberg passes along invaluable wisdom gleaned from his years of experience in academia. Dr. Sternberg has distilled his analysis of choices made over a long and singularly successful career into rich, densely packed maxims that will help students and new academics create a foundation for a gratifying career of their own. This book will also be immensely useful to those interested in advancing in their careers or those who want to find new meaning their work. Dr. Sternberg's advice gives readers a template for learning how to make lasting marks on-and significant contributions to-the academic world of psychology while still following their hearts. The thoughtful lessons this book offers will be highly valued by students, young psychologists, and career academicians. It is sure to become an enduring companion that readers will return to time and again.